P078: Derivation and validation of a non return to work predictive model three months after a mild traumatic brain injury. (15th May 2017) - Le Sage, N.; Chauny, J.; Émond, M.; Moore, L.; Archambault, P.M.; De Guise, É.; Ouellet, M.; Tardif, P.; Mercier, E.
Abstract : Introduction: Mild traumatic brain injury (mTBI) is a common problem and until now, ED physicians don't have any tool to predict when the patient will return to work. The purpose of this study is to develop and validate a clinical decision rule to identify the ED patients who are at risk of non-return to work or to school three months after a mTBI.Methods: Patients were recruiting in five Level I and II Trauma Centers ED in the province of Québec. All patients were referred for a systematic telephone follow-up after three months. Information about their return to work/school, partial or complete, was collected. Log binomial regression was used to develop a predictive model and the validation of this model was performed on a different prospective cohort.Results: 13, 7% of the patients did not return to work/school at three months. The final model was derived from a prospective cohort of 398 patients and included three risk factors: motor vehicle accident (2 points), loss of consciousness (1 point) and headache during the emergency department assessment (1 point). With a one-point threshold, this model has a sensitivity of 97% and a negative predictive value (NPV) of 98%. However, the specificity is only 23% and the positive predictive value (PPV) is 17%. The area under the curve is 0.786. Validation of the model was performed with a new prospective cohort of 517 patients, and demonstrated a sensitivity of 86% and a NPV of 91%.Conclusion: Although this model is not very specific, its high sensitivity and NPV indicate to the clinician that mTBI patients who don't have any of the three criteria are at low risk of prolonged work stoppage after their trauma.